Pengaruh Live Streaming Dan Diskon Terhadap Minat Beli Konsumen Shopee Pada Mahasiswa Universitas Jambi - Ilham Ramadhan (Universitas 45 Surabaya, 2024)
The fierce business competition in the shopee requires sellers to undertake promotional strategies that can attract consumer interest in buying their products. Therefore, this study was conducted to analyse the impact of live streaming and discounts on purchasing interest in Jambi University students. By using the method of causal quantitative research it is possible to know how the influence of live streaming and discount variables as independent variables on the purchasing interest variable as dependent variables. Out of a total of 30,988 students as a population, only 100 Jambi University students were taken as samples. The data collected through the questionnaire is then analyzed using the evaluation of the measurement model (outer model), the assessment of the structural model (inner model), and the test of the hypothesis. Later from the results of the research it was found that partially live streaming has an influence on buying interest, so with Discount which partially also has an impact on purchasing interest, and simultaneously live streaming and Discount can affect Shopee consumer buying interest in Jambi University Students.